Prenatal Ultrasound Diagnostics of Autosomal Recessive Polycystic Kidney Disease in Fetus: Clinical Case - Nodira M. Normuradova; Mirtalim А. Pardaev (Вопросы современной педиатрии, 2022)
Background. Autosomal recessive polycystic kidney disease is a rare congenital anomaly with poor prognosis. It characterized by the development of cysts in kidneys parenchyma, secondary dilatation, and hyperplasia of normally formed collecting tube in kidneys.Clinical case description. Autosomal recessive polycystic kidney disease was diagnosed in the fetus via ultrasound in the third trimester of pregnancy, signs of “large hyperechogenic kidneys” were revealed. The fetal kidneys were significantly enlarged, the parenchyma was thickened, and there was no cortico-medullary differentiation. The renal pelvises and bladder were identified. Amniotic fluid volume was normal. The ultrasound diagnosis was confirmed with magnetic resonance imaging. Female child born at full term, weight — 4500 grams, she was discharged home in satisfactory condition. At the age of 7 months, child physical development corresponds to her age. Ultrasound examination shows the persistence of pronounced increase in the size of kidneys, parenchyma thickening and no cortico-medullary differentiation. The renal pelvises and bladder are not dilatated. Urine analysis results: epithelia in large quantities, single leukocytes and isomorphic erythrocytes, as well as protein of 0.066 g/l. Blood creatinine and blood urea were within normal ranges.Conclusion. Amniotic fluid volume and presence of urine in the bladder are the most important characteristics of the kidney functioning in case of antenatal ultrasound signs of autosomal recessive polycystic kidney disease. The absence of amniotic fluid at visualization of “large hyperechogenic kidneys” is considered as poor prognostic feature. MRI is crucial to clarify the diagnosis of autosomal recessive polycystic kidney disease and allows adequately estimate the amniotic fluid volume in the third trimester of pregnancy.